Corpo Silenciado, Voz Silenciada: Análise Do Discurso Dos Homens Transexuais Sobre O Atendimento No Sistema Único De Saúde (PERcursos Linguísticos, 2020)
The present work aims to analyze the discourse of two trans men who treated the Unified Health System. Their experiences were reported through interviews. Therefore, we will apply the assumptions of the Materialist Discourse Analysis that had as one of the precursors Michel Pêcheux, in France, and Eni Orlandi, in Brazil. We’ll the concept of Silence, Discourse, identification and counter-identification. At last, we will realize that there is still much to consolidate in the inclusion of the transsexual community in order to have full service and respect in the care units of the Brazilian Unified Health System.